The Visual, Auditory, and Physical Environment of Livestock Handling Facilities and Its Effect on Ease of Movement of Cattle, Pigs, and Sheep - Grandin, Temple (Frontiers in Animal Science, 2021)
The visual, auditory, and physical environment livestock are handled in will have an effect on the ease of movement through races and corrals that are used for veterinary treatment, loading trucks or at slaughter houses. When livestock refuse to move easily through a handling facility, people are more likely to use electric goads (prods) or other aversive methods to move them forward. This is a major animal welfare concern. Modification of the environment can improve livestock movement and reduce aversive handling methods. In existing facilities used for handling cattle, pigs or sheep, simple changes such as, adding a light to a dark race entrance or reducing loud intermittent noise may improve livestock movement. Eliminating distractions such as, a noisy truck near a lairage can also facilitate cattle movement and reduce stopping or turning back. In an outdoor facility, sharp shadows on the floor were more likely to be associated with cattle stopping compared to no shadows or soft faint shadows. The installation of small solid walls to prevent approaching animals from seeing either moving equipment, vehicles or people in front of them may also improve forward livestock movement. Non-slip flooring is essential to prevent slipping and falling during handling. Rebuilding or completely redesigning an existing facility is often not required. Outcome based indicators should be used to assess continuous improvements in handling. Some of the commonly used measurable of handling are slipping and falling, stopping, turning back, vocalization during handling and electric prod use. Collecting data both before and after an environmental modification can be used to determine its effectiveness.